Drug Use in Night Owls May Increase the Risk for Mental Health Problems - Fernando, Jeevan; Stochl, Jan; Ersche, Karen D. (Frontiers in Neuroscience, 2022)
Drugs of abuse are widely known to worsen mental health problems, but this relationship may not be a simple causational one. Whether or not a person is susceptible to the negative effects of drugs of abuse may not only be determined by their addictive properties, but also the users’ chronotype, which determines their daily activity patterns. The present study investigates the relationship between chronotype, drug use and mental health problems in a cross-sectional community sample. Participants (n = 209) completed a selection of questionnaires online, including the Munich Chronotype Questionnaire, the Depression Anxiety Stress Scale, the Alcohol Use Disorder Identification Test, the Cannabis Use Disorder Identification Test and the Fagerström Test for Nicotine Dependence. We conducted multiple regression models to determine relationships between participants’ chronotype and their reported mental health symptoms and then estimated mediation models to investigate the extent to which their drug consumption accounted for the identified associations. Chronotype was significantly associated with participants’ overall mental health (β = 0.16, p = 0.022) and their anxiety levels (β = 0.18, p = 0.009) but not with levels of depression or stress. However, both relationships were fully mediated by participants’ overall drug consumption. Thus, late chronotypes, so-called “night owls”, not only use more drugs but consequently have an increased risk for developing anxiety and deteriorating mental health status. This group may be particularly vulnerable to the negative psychological effects of drugs. Our results point toward the importance of considering chronotype in designing preventative and therapeutic innovations, specifically for anxiety, which at present has been largely neglected.